Leveraging Vulnerability and Adaptability Assessments to Enhance Fire Safety in Sungai Asap Longhouses, Sarawak - Andre Kueh, Richard Mering; Salfarina, Abdul Gapor; Mohd Zulhafiz, Said; Azizul, Ahmad (RSIS International, 2025)
Longhouses in Sarawak are susceptible to fire incidents, and limited research has been conducted on their vulnerability and adaptability to fire hazards. Therefore, this paper aims to examine the vulnerability and adaptability level of longhouses in Sungai Asap to fire hazards. A quantitative approach was conducted. A sampling of 59 respondents was interviewed through a survey and data are analysed using frequency test. The findings revealed that three longhouses were in the category of at-risk while the other three were vulnerable. Fire risks were related with the usage of electricity, inadequate fire safety features, and the proneness of building materials to fire. Recommendations to reduce vulnerability include regular awareness programmes on fire safety, engagement of a certified chargemen and changing to less prone building materials. The findings can assist in improving longhouse fire safety in Sarawak and as a framework to develop guidelines for designing new communal dwellings.